It's Private: Introductory Comments on "First Encounters with Erotic Desire in Treatment". Issue 1 (2nd January 2019) - Slavin, Jonathan H.
Abstract : The human tendency to assert and maintain a certain privacy of mind, from others but also from oneself, is an adaptive and essential aspect of psychic functioning. Yet the psychoanalytic process asks patients to relinquish that privacy of mind, including one's sexual privacy, to accomplish its therapeutic aims. This introductory essay to an important paper and discussions of the therapist's sexual experiencing considers questions of therapists' privacy and the circumstances for relinquishing it.